2001
DOI: 10.1016/s0735-1097(01)01556-x
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive detection of total occlusion of the left anterior descending coronary artery with transthoracic Doppler echocardiography

Abstract: Retrograde flow in the LAD by TTDE is a highly sensitive and specific finding that can be used to noninvasively diagnose total LAD occlusion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(34 citation statements)
references
References 21 publications
0
33
1
Order By: Relevance
“…Nevertheless, the TDE finding of retrograde diastolic flow, either in the epicardial vessel or in perforating branches, is a useful and specific sign of coronary occlusion. The reasons for the discrepancy between our data and those of others 9,10 are not clear, but patient selection, racial difference in chest wall acoustic impedance, and coronary flow sampling site by TDE may play a role. In our population, there was also some discrepancy between the direction of flow when detected at angiography or by TDE.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…Nevertheless, the TDE finding of retrograde diastolic flow, either in the epicardial vessel or in perforating branches, is a useful and specific sign of coronary occlusion. The reasons for the discrepancy between our data and those of others 9,10 are not clear, but patient selection, racial difference in chest wall acoustic impedance, and coronary flow sampling site by TDE may play a role. In our population, there was also some discrepancy between the direction of flow when detected at angiography or by TDE.…”
Section: Discussioncontrasting
confidence: 99%
“…A possible explanation may be that Werner et al 12 included patients with previous myocardial infarctions of the index artery, whereas Watanabe et al 9 and we studied only patients without previous infarctions of the myocardium distal to the occluded artery. In addition, there may be some pitfalls in the measurement of collateral flow by intracoronary Doppler flow wire: (1) it is technically demanding, (2) the position of the tip of the wire relative to the occlusion and to the input of collateral flow may be suboptimal, (3) sampling too close to the occlusion site may result in small coronary flow velocity recordings, (4) artifacts may be generated by guidewire motion and inadvertent contact with the vessel wall, 13 and (5) placing the Doppler wire requires a previous opening of the vessel with a stiff wire, which creates a new channel, potentially altering collateral flow dynamics.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…However, it has been reported that total LAD occlusion can be detected on TTE. 58) These reports have shown that the sensitivity and specificity of TTE in identifying LAD occlusion are almost 100%. 58)59) However, it is very difficult to apply this TTE technique to the LCX or RCA.…”
Section: Evaluation Of Coronary Atherosclerosismentioning
confidence: 98%